Biodistribution analysis of cisplatin in liposomal form in animals with cisplatinresistant and cisplatin-sensitive carcinoma - Nosko, M.M.; Pivnyuk, V.M.; Solyanik, G.I.; Kulik, G.I.; Todor, I.N.; Momot, V.Ya.; Melnikov, O.R.; Ponomareva, O.V.; Chekhun, V.F. (Experimental Oncology, 2010)
Aim: To analyze the relation between pharmacokinetics of cisplatin in liposomal form and antitumor efficacy toward cisplatinresistant and cisplatin-sensitive variants of Guerin carcinoma. Concentration of platinum was measured by atomic absorption spectrophotometry (С115М1 “Selmi”, Ukraine). Elimination constant was calculated based on the dynamics of cisplatin concentration in time period between 1 h to 24 h using nonlinear regression analysis. Area under curve (AUC24) was calculated by the trapezium method. Results: It was shown that for liposomal form of cisplatin (LCp) AUC24 in tumor practically didn’t depend on the level of the tumor sensitivity, while in animals with the resistant variant (CpRGC), AUC24 for free cisplatin (FCp) decreased by 70% less (p < 0.001) as compared to the sensitive tumor strain (CpSGC). Significant decrease of elimination constant of LCp compared to FCp in blood serum of rats bearing either CpRGC or CpSGC tumors favors cisplatin accumulation in tumor tissues with low vascularization level. The dynamics of cisplatin concentration in CpRGC variant was characterized by 90% higher level in 24 h after administration of LCp as compared to FCp (p < 0.05). This fact may explain increased antitumor efficacy of LCp compared to FCp toward CpRGC variant. In the study of kidney function, AUC24 index for LCp was by 68.6% (p < 0.01) and 50.7% (p < 0.05) lower than AUC24 index for FCp in rats with CpRGC and CpSGC variants, respectively. No significant differences have been found in biodistribution of cisplatin in both pharmaceutical forms in liver and lung in CpRGC-r CpSGC-bearing rats. Conclusion: The results suggest that cisplatin in liposomal form possesses higher specificity of antitumor action than free cisplatin.